Lavender : 50 self-care recipes and projects for natural wellness - Gillis, Bonnie Louise, 1958- (Sasquatch Books, 2021)
"Includes 50 Recipes for Food, Handcrafted Gifts, Household and Body Care Products and Natural Remedies with Fresh, Dried and Essential Oil Lavender"--